1987
DOI: 10.1002/dev.420200504
|View full text |Cite
|
Sign up to set email alerts
|

Intersensory coordination and the effects of early sensory deprivation

Abstract: The effect of early visual deprivation on the ability of dark- (DR) and light-reared (LR) rats to learn temporal discriminations involving sounds and lights and to abstract the intersensory correspondence involving duration from initial modality-specific training was examined in this study. While visually inexperienced DR rats were somewhat less successful in acquiring an initial discrimination involving visual events and responding to a rule reversal per se, they were as effective as their visually experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
(17 reference statements)
2
14
1
Order By: Relevance
“…Since the cortical dendritic arbor of pyramids is the main area associated with the effects of sensorial experience, the neuronal alterations documented here may possibly interfere with the planning and execution of movements in order to modulate adaptive motor and postural performance in infants. In this regard, our findings are in line with previous studies showing electrophysiological alterations, reductions in the number of spines, dendritic prolongations and synaptic contacts following whisker clipping, immobilization or reduced maternal and environmental sensory deprivation or associated with the chronic exposure to stress environments (Tees and Symons 1987, Watanabe et al 1992, Pascual et al 1993, King and Hill 1993, Keller and Carlson 1999, Gould et al 2000, Erchova et al 2003, Farmer et al 2004 or the opposite neuronal effects in animals exposed to sensory enriched environmental conditions ( Juraska 1983, Pascual and Figueroa 1996, Rosenzweigh and Bennett 1996. Postural and motor capabilities are adaptive multisensory-dependent, responses to numerous environmental demands.…”
supporting
confidence: 93%
“…Since the cortical dendritic arbor of pyramids is the main area associated with the effects of sensorial experience, the neuronal alterations documented here may possibly interfere with the planning and execution of movements in order to modulate adaptive motor and postural performance in infants. In this regard, our findings are in line with previous studies showing electrophysiological alterations, reductions in the number of spines, dendritic prolongations and synaptic contacts following whisker clipping, immobilization or reduced maternal and environmental sensory deprivation or associated with the chronic exposure to stress environments (Tees and Symons 1987, Watanabe et al 1992, Pascual et al 1993, King and Hill 1993, Keller and Carlson 1999, Gould et al 2000, Erchova et al 2003, Farmer et al 2004 or the opposite neuronal effects in animals exposed to sensory enriched environmental conditions ( Juraska 1983, Pascual and Figueroa 1996, Rosenzweigh and Bennett 1996. Postural and motor capabilities are adaptive multisensory-dependent, responses to numerous environmental demands.…”
supporting
confidence: 93%
“…35 For example, the bobwhite quail maternal call is an extremely compelling stimulus for young quail hatchlings, easily outweighing the effects of species-typical maternal visual cues during early postnatal development. 65 A similar pattern of the initial salience of auditory over visual information has also been reported for domestic chicks, 66 ducklings, 67 ± 69 rats, 70 lambs, 71 and human infants. 72 ± 74 Several studies manipulating either prenatal auditory or prenatal visual experience 34,35,44,75 have indicated that this typical pattern of the initial salience of auditory over visual information can be redirected.…”
Section: Sensory Experience and Stimulus Saliencesupporting
confidence: 73%
“…In animal studies, early sensory deprivation caused decreased axonal and dendritic branches between functionally connected neurons (Bryan and Riesen 1989), decreased discriminative acuity (Murphy and Mitchell 1991; Tusa, et al 1991), and decreased complex sensory-processing (Tees and Midgley 1978; Tees and Symons 1987). Thus, sensory inputs typically impact development of cortical function and structure.…”
Section: Discussionmentioning
confidence: 99%